Lignocellulose biomass delignification using acid hydrotrope as green solvent : A mini-review - Nur Izzah Atirah, Mat Hussain; Nurjannah, Salim; Siti Noor Hidayah, Mustapha; Izan Izwan, Misnon; Mohd Hasbi, Ab Rahim; Rasidi, Roslan (Publishing House of the Romanian Academy, 2023)
Efficient and cost-effective conversion of lignocellulosic biomass into usable forms of energy presents unique challenges. Lignocellulosic biomass, comprising cellulose, hemicelluloses, and lignin, necessitates advanced conversion technologies. Common commercial delignification techniques, including kraft pulping, sulfite pulping, acid hydrolysis, and organosolv pulping, often involve harsh conditions leading to structural changes in lignin and environmental impacts. To address these issues, acid hydrotropes have emerged as a promising method for lignin extraction. Acid hydrotropes, represented by p-toluenesulfonic acid (p-TsOH), enable the solubilization of hydrophobic substances like lignin. This mini-review provides an overview of various lignocellulose fractionation techniques and explores the acid hydrotrope approach. The mechanism behind acid hydrotropic fractionation is discussed, and its performance is evaluated. In conclusion, the review emphasizes the pivotal role of the acid hydrotrope approach in advancing lignocellulosic biomass conversion technology, promoting a sustainable and efficient bio-based economy.